CuO-Loaded Macroreticular Anion Exchange Hybrid Polymers Obtained via Tetrachlorocuprate(II) Ionic Form - Elżbieta Kociołek-Balawejder; Ewa Stanisławska; Irena Jacukowicz-Sobala; Daniel Ociński (International Journal of Polymer Science)
Amberlite IRA900 Cl, the macroreticular, polystyrene/divinylbenzene anion exchanger containing quaternary ammonium groups, was used as the support for copper(II) oxide deposition, and, as a result a new hybrid ion exchanger (HIX) was obtained. The CuO deposit was introduced into the anion exchanger structure in two steps conducted batchwise at ambient temperature. First, the functional groups were transformed from the Cl- into the CuCl42- form, using 5 mol dm−3 NaCl or HCl solution with CuCl2 being added, and then the intermediate product was contacted with NaOH/NaCl solution to precipitate CuO within the polymer beads. A HIX containing as much as 11.5% Cu was obtained. The distribution of the inorganic load within the porous matrix of polymer beads was atypical; CuO was mainly deposited in the outer parts of the beads and only a small amount was in their inner parts. This may be advantageous in some practical applications concerning the removal of harmful admixtures from waters in sorption processes.